Tridentate Lewis Acids: Boron‐, Silicon‐ and Gallium‐Functionalised Tris(dimethylsilyl)methanes. Issue 8 (18th February 2016) - Weisheim, Eugen; Schwartzen, Anna; Kuhlmann, Lisa; Neumann, Beate; Stammler, Hans‐Georg; Mitzel, Norbert W.
Abstract: Flexible tridentate Lewis acids based on new trisilylmethane scaffolds with three ethynyl groups {Me3 SiC[Si(Me)2 C≡C–H]3 } and three vinyl groups {Me3 SiC[Si(Me)2 CH=CH2 ]3 }, respectively, have been synthesised and functionalised by metallation with gallium organyls to yield Me3 SiC[Si(Me)2 C≡C–GaR2 ]3 (R = Me, Et). Hydrometallation of the trisilylmethane frameworks with HB(C6 F5 )2 and various chlorosilanes afforded flexible poly‐Lewis acids equipped with B(C6 F5 )2, SiCl3, SiMeCl2 and SiMe2 Cl substituents. The reaction of these silicon‐containing tridentate Lewis acids with SbF3 led to fluorine‐substituted poly‐Lewis acids of the type Me3 SiC[Si(Me)2 CH2 CH2 SiMe3– n F n ]3 ( n = 1–3). All the compounds were characterised by multinuclear NMR spectroscopy, mass spectrometry, elemental analyses and some by X‐ray diffraction. Abstract : New tridentate Lewis acids based on tris(dimethylsilyl)trimethylsilylmethane scaffolds equipped with ethynyl and vinyl groups have been synthesised. They were functionalised with GaMe2 and GaEt2 groups by alkane elimination, with B(C6 F5 )2 and SiCl n Me3– n groups by hydrometallation reactions and with SiF n Me3– n groups by substitution of the chlorine atoms by fluorine.